2010
DOI: 10.1029/2009jd013306
|View full text |Cite
|
Sign up to set email alerts
|

First observation‐based estimates of cloud‐free aerosol radiative forcing across China

Abstract: [1] Heavy loading of aerosols in China is widely known, but little is known about their impact on regional radiation budgets, which is often expressed as aerosol radiative forcing (ARF). Cloud-free direct ARF has either been estimated by models across the region or determined at a handful of locations with aerosol and/or radiation measurements. In this study, ARF is determined at 25 stations distributed across China where aerosol optical thickness has been measured since 2004. In combination with the single-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 122 publications
(71 citation statements)
references
References 59 publications
3
57
3
3
Order By: Relevance
“…Asian Pacific Regional Aerosol Characterization Experiment (ACE-Asia) (Huebert et al, 2003), the Asian Atmospheric Particle Environment (APEX) (Nakajima et al, 2003), the East Asian Study of Tropospheric Aerosols: An International Regional Experiment (EAST-AIRE) (Li et al, 2007) and cloud-free aerosol radiative forcing across China (Li et al, 2010). In recent years, many studies have been undertaken to assess the impact of aerosols on the climate in the Indian region Ramanathan et al, 2001b;Moorthy et al, 2005;Ramachandran, 2005aRamachandran, , 2005bTripathi et al, 2005;Pant et al, 2006;Niranjan et al, 2007;Babu et al, 2007;Sreekanth et al, 2007;Dey and Tripathi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Asian Pacific Regional Aerosol Characterization Experiment (ACE-Asia) (Huebert et al, 2003), the Asian Atmospheric Particle Environment (APEX) (Nakajima et al, 2003), the East Asian Study of Tropospheric Aerosols: An International Regional Experiment (EAST-AIRE) (Li et al, 2007) and cloud-free aerosol radiative forcing across China (Li et al, 2010). In recent years, many studies have been undertaken to assess the impact of aerosols on the climate in the Indian region Ramanathan et al, 2001b;Moorthy et al, 2005;Ramachandran, 2005aRamachandran, , 2005bTripathi et al, 2005;Pant et al, 2006;Niranjan et al, 2007;Babu et al, 2007;Sreekanth et al, 2007;Dey and Tripathi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that unpolluted Aeolian dust (sourced from northwest China) is not largely absorbing. Li et al (2010) pointed out that despite intensive efforts to elucidate the optical properties and radiative forcing of aerosol across China, the northwestern region has been poorly sampled and thus neglected. Huang et al (2007Huang et al ( , 2009) studied the vertical distribution and heating rate of dust aerosol over the Taklimakan Desert, combining the Fu-Liou radiative transfer model with satellite observations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to characterize the aerosol optical properties based on observations in China, as many studies did in recent years at urban sites and in rural areas (e.g. Bergin et al, 2001;Xu et al, 2002Xu et al, , 2004Xu et al, , 2012Zhang et al, 2004Zhang et al, , 2015Yan, 2006;Xia et al, 2007;Yan et al, 2008;Andreae et al, 2008;He et al, 2009;Wu et al, 2009Wu et al, , 2012Wang et al, 2009;Li et al, 2010;Fan et al, 2010;Bai et al, 2011;Cai et al, 2011;Xiao et al, 2011;Zhuang et al, 2015;Li et al, 2015a, b;Yu et al, 2016). For example, Bergin et al (2001), and Zhuang et al (2015) presented the surface aerosol scattering and absorption properties in urban area of north and east China and they suggested that the annual mean 532 nm AAC (aerosol absorption coefficient) in Beijing was about 56 Mm −1 and it was 41-44 Mm −1 in YRD, which were much smaller than those in central to south-west China and in PRD (Wu et al, 2009;Cao et al, 2012;Tao et al, 2014) but much larger than those in rural and desert regions (Xu et al, 2002(Xu et al, , 2004Yan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%